Prevalence of Overweight and Obesity among Primary Healthcare Workers In Perak, Malaysia - Kit, Low Pei; Abu Saad, Hazizi; Jamaluddin, Rosita; Phing, Chee Huei (IIUM Medical Journal Malaysia, 2020)
Introduction: Overweight and obesity has been emerging as one of the most common and preventable nutritional problems worldwide. In 2016, 39% and 13% of the adult population worldwide was classified as overweight and obese, respectively. Materials and Methods: We conducted a cross-sectional study at 12 selected health clinics in Perak, Malaysia, and we used multi-stage cluster random sampling to determine the prevalence of overweight and obesity among the primary healthcare workers and the associate factors of obesity indices. Each respondent was required to complete a self-administered questionnaire on their socio-demographic characteristics. In addition, we took anthropometric measurements, including height, weight, BMI, waist circumference, and body fat percentage, of the participants. Results: We recruited 261 primary healthcare workers. Overall, 49.9% of the healthcare workers were overweight or obese, 51.0% were at risk of having abdominal obesity, and 79.6% had a high body fat percentages. Age and self-reported health status were significantly associated with all the obesity indices. Educational level showed significant association with BMI and waist circumference, while occupational status showed an association only with BMI. Older age and professionals were predictors for high obesity indices. Conclusion: The prevalence of obesity among the primary healthcare workers was higher than among the general population. An immediate intervention programme is needed to reduce the prevalence of overweight and obesity among primary healthcare workers.